Spatial ecology : the role of space in population dynamics and interspecific interactions - Tilman, David, 1949-; Kareiva, Peter M., 1951- (Monographs in population biology ;, 1997)
"Spatial Ecology addresses the fundamental effects of space on the dynamics of individual species and on the structure, dynamics, diversity, and stability of multispecies communities. Although the ecological world is unavoidably spatial, there have been surprisingly few attempts to determine how explicit considerations of space may alter the predictions of ecological models, or what insights they may give into the causes of broad-scale ecological patterns. As the chapters in this book demonstrate, the spatial structure of a habitat can fundamentally alter both the qualitative and quantitative dynamics and outcomes of ecological processes." "Spatial Ecology is designed to highlight the importance of space to five topical areas: stability, patterns of diversity, invasions, coexistence, and pattern generation. Its aim is to illustrate both the diversity of approaches used to study spatial ecology and the underlying similarities of these approaches."--Jacket